A Study of the Potential of Ecotourism Development in Konawe Islands Regency, Southeast Sulawesi Province, Indonesia - Hidrawati Hidrawati; Normayasari Normayasari; Sariamin Sahari; Samsul Alam Fyka; Wa Ode Yusria (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
The ecotourism potential development in Konawe Islands, Southeast Sulawesi Province requires academic study as a foothold in region policy making by all development stakeholders. This study aims to provide data and information about the potential of natural resources could be the ecotourism object, analyzing the perceptions of local communities, and formulating strategic plan for ecotourism development. The study was conducted from April-October 2019. This research used quantitative methods with data that were collected from observations, interviews, Focus Group Discussion (FGD) and literature studies. Data analysis was made using quality criteria scale of flora fauna diversity, SWOT analysis and litmus tests. The results of the study showed that Konawe Islands Regency has potential ecotourism objects in coastal-sea panoramas (Sawaea beach and Kampa beach), and in the mainland-hills with waterfalls panoramas (Tumburano waterfalls and Lanuku waterfalls). The results of importance/significance measurements indicate that the flora potential have a scale value of 3 (moderate), the fauna potential have scale of value 4 (good) and the potential criteria of